The Impacts of Gender-Related Factors on the Adoption of Anti-Human Trafficking Laws in Sub-Saharan African Countries - Byung-Deuk Woo (SAGE Open, 2022)
Human trafficking is an imminent problem not limited to certain regions of the globe. Although the problem of human trafficking is severe over the world, Sub-Saharan African countries are some of the most vulnerable to human trafficking. Despite the severity of human trafficking in Sub-Saharan Africa, only 23 countries, less than half of Sub-Saharan African countries, have introduced domestic statutory laws addressing human trafficking. Why do some African countries adopt laws for combating human trafficking, while others do not? Focusing on the role of gender-related factors in the introduction of laws addressing human trafficking, this article aims to fill this academic lacuna by conducting time-series cross-national analysis on 49 African countries from 1960 to 2016. The empirical results from this study demonstrate that increases in the percentage of women in legislative branches and in women’s participation in civil society organizations lead countries to introduce anti-human trafficking laws.